Efeito da Prometazina isolada e em associação a antibacterianos frente à cepas de Staphylococcus aureus e sua ação preventiva na formação de biofilmes em cateter de silicone - Costa, Érica Rayanne Mota da (2024)
Urinary infections caused by Staphylococcus aureus are commonly associated with urinary catheterization and often result in severe complications. The occurrence of antimicrobial resistance (AR) in these isolates makes the clinical management of infections even more challenging. In this context, drug repositioning is a strategy that represents a viable alternative to the discovery of new antimicrobials. Due to its action on various receptors, promethazine, a first-generation antihistamine, is a constant target of studies aimed at exploring new pharmacological properties. Given this problem, the objective of the study was to evaluate the antimicrobial activity of promethazine, alone and in combination with oxacillin and vancomycin, against planktonic cells and biofilms of Staphylococcus aureus, and to investigate its preventive action against the formation of methicillin-resistant Staphylococcus aureus biofilm when impregnated in urinary catheters. For this purpose, the broth microdilution technique was used, according to the 2015 CLSI M07-A10 protocol, to determine the Minimum Inhibitory Concentration (MIC). Subsequently, tests were conducted to establish the Minimum Bactericidal Concentration (MBC) and the tolerance level of promethazine. The checkerboard technique was applied to analyze the interaction between the drugs. Additionally, a flow cytometry assay was conducted to investigate the possible mechanism of action of the drug. The efficacy of promethazine against already formed and forming biofilms was also observed through the reduction assay of tetrazolium blue thiazolyl bromide (MTT), as well as its preventive action impregnated in urinary catheter fragments through colony counting. Finally, Scanning Electron Microscopy (SEM) was used to analyze the morphological changes induced by promethazine. Promethazine showed bactericidal antimicrobial activity with MIC values ranging from 170.6 to 256 µg/mL, predominantly additive interaction in combination with oxacillin and vancomycin, and reduction of cell viability of forming and formed biofilms of methicillin-sensitive and methicillin-resistant S. aureus. Morphological changes, membrane damage, and genetic material damage were also observed in cells treated with promethazine. The results allowed us to infer that promethazine can be classified as a promising antimicrobial agent for use in the antibacterial coating of long-term urinary devices